Correction: Shear-induced polydomain structures of nematic lyotropic chromonic liquid crystal disodium cromoglycate. Issue 21 (19th May 2021) - Baza, Hend; Turiv, Taras; Li, Bing-Xiang; Li, Ruipeng; Yavitt, Benjamin M.; Fukuto, Masafumi; Lavrentovich, Oleg D.
Abstract : Correction for 'Shear-induced polydomain structures of nematic lyotropic chromonic liquid crystal disodium cromoglycate' by Hend Baza et al., Soft Matter, 2020, 16, 8565–8576.